Detection of Circulating Tumor DNA in Patients with Thyroid Nodules. (24th August 2021) - Patel, Krupal B.; Cormier, Nicholas; Fowler, James; Partridge, Allison; Theurer, Julie; Black, Morgan; Pinto, Nicole; Yoo, John; Fung, Kevin; MacNeil, Danielle; Stecho, William; Howlett, Christopher; et al.
Abstract : Objective . Detection of circulating tumor DNA (ctDNA) in cancer patients can potentially serve as a noninvasive, sensitive test of disease status. The purpose of this study was to determine the ability to detect BRAF (V600E) mutations in the plasma of patients with thyroid nodules, with the goal of distinguishing between benign and malignant nodules. Methods . Consecutive patients with thyroid nodules who consented for surgery were recruited. Plasma samples were obtained preoperatively and one month postoperatively. Quantitative PCR was used to determine the levels of the BRAF (V600E) mutation preoperatively and postoperatively. Results . A total of 109 patients were recruited. On final pathology, 38 (32.8%) patients had benign thyroid nodules, 45 (38.8%) had classical papillary thyroid cancer (PTC), 23 (19.8%) had nonclassical PTC, and 3 (2.6%) had follicular thyroid cancer. 15/109 patients had detectable BRAF (V600E) ctDNA in their preoperative samples—all of them having classical PTC. Higher T-stage and extrathyroidal extension in PTC were associated with positive BRAF (V600E) ctDNA (p < 0.05 ). Eighty-eight pairs of preoperative and postoperative plasma samples were collected and analyzed. Of these eighty-eight paired samples, a total of 13/88 (14.8%) patients had detectable BRAF (V600E) ctDNA in their preoperative samples—all of them having classical PTC. 12 of these 13 patients had no detectable BRAF (V600E) postoperatively, while one remaining patient had a significant decline in his levels (p < 0.05 ). Conclusion . BRAF (V600E) circulating thyroid tumor DNA can be detected in plasma and is correlated with a final diagnosis of the classical variant of PTC. Given that a postoperative drop in BRAF (V600E) ctDNA levels was observed in all cases suggests its utility as a tumor marker.